2001
DOI: 10.1177/146642400112100108
|View full text |Cite
|
Sign up to set email alerts
|

Comfort and health in commercial aircraft: a literature review

Abstract: Air travel is becoming increasingly more accessible to people both through the availability of cheap flights and because the airlines are now able to cater for individuals of all ages and disabilities. The wide bodies of many new aircraft permit the airlines to have very flexible seating options. Airline operators currently have an important role in determining the comfort and spaciousness of the seating in their aircraft. Passengers who remain seated for the bulk of a flight may risk oedema or deep vein throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…This may be due to local hypoxia, which causes vasodilation and increased capillary permeability. The ventilation system of aircraft is determined by the required air quality rather than the oxygen supply, for example to dilute human body odour and CO 2 to an acceptable level [11]. There is a paucity of data, however, on the quality of this air and on the effect of this quality on the S p O 2 of the individual passengers.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to local hypoxia, which causes vasodilation and increased capillary permeability. The ventilation system of aircraft is determined by the required air quality rather than the oxygen supply, for example to dilute human body odour and CO 2 to an acceptable level [11]. There is a paucity of data, however, on the quality of this air and on the effect of this quality on the S p O 2 of the individual passengers.…”
Section: Discussionmentioning
confidence: 99%
“…38 Although passenger airplanes maintain a cabin pressure that does not require supplementary oxygen (equivalent to an altitude of 1524-2438 m), healthy individuals still experience a reduction in oxygen saturation level in the hemoglobin. 39 Occlusion of the cerebral veins, presenting with headache and behavioral abnormalities, can occur in travelers on long-distance airplane flights. 40 It has been suggested that prolonged air travel in a cabin pressurized to the equivalent of high altitude might result in compensatory hemoconcentration and increased blood viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research indicates that long distance air travel can increase the possibility of cross-infection of disease (Spengler & Wilson, 2003). This is particularly the case where there are lower air ventilation rates in the aircraft cabin (Brundrett, 2001). It is advisable for international business travelers to take medical supplies with them during their journey (Deacon & McCulloch, 1990).…”
Section: Healthmentioning
confidence: 99%